EGR thermal and chemical effects on combustion and emission of diesel/natural gas dual-fuel engine. (15th October 2021) - Zhang, Wei; Feng, Ting; Li, Zehong; Chen, Zhaohui; Zhao, Jianming
Highlights: EGR combined effect is the sum of the thermal and chemical effects. EGR thermal effect is greater than the chemical effect. The influence of dual-fuel combustion on EGR is more sensitive. The influence of CO2 on key components is greater than that of H2 O. The impact factors of CO2 and H2 O together are the sum of the two separation. Abstract: In this paper, by coupling a D19 diesel engine three-dimensional and one-dimensional models with a diesel/NG dual-fuel chemical dynamics mechanism, respectively, the thermal and chemical effects of the EGR major components (CO2 and H2 O) on in-cylinder combustion and emissions were studied. The results show that the EGR combined effect is the sum of the thermal and chemical effect, and the thermal effect is greater than the chemical effect. In the EGR major components, the CO2 thermal effect is greater than that H2 O, and the chemical effect is smaller than that H2 O. At the 50% EGR rate, CO2 and H2 O thermal and chemical effects accounted for 65.3% and 36.7% of the combined effects in diesel mode, respectively. At the 50% EGR rate, the thermal and chemical effects of CO2 and H2 O accounted for 62.2% and 39.2% of the combined effects in dual-fuel mode, respectively. The effects of CO2 and H2 O can be superimposed with each other. CO2 and H2 O have a greater influence in dual-fuel mode, that is, the dual-fuel is more sensitive to EGR.